The creation of the work of art: A path full of challenges - Dos Santos Cunha, María José (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
What moved us in carrying out this work was the need to make a reflection to better understand the process of creation of the artistic work and the role ― in making the constructed object known to us ― of genetic criticism, a mainstay methodology in the study of creation processes. This reflection of ours, which was methodologically based on a bibliographic search on authors who wrote about the topics, allowed us to have a better understanding of the goals we set for ourselves.